Association between red blood cell distribution width and encephalitis based on the pediatric intensive care unit database: a cross-sectional study - He, Weichao; Yang, Qilin; Jiang, Rui; Yang, Xinyu; Zhang, Xujie; Cao, Ruoyu; Liu, Xiaojuan; Tong, Shanshan (Frontiers in Neurology, 2025)
BackgroundEncephalitis is an inflammatory disease of the brain parenchyma that continues to affect populations worldwide, with high morbidity and risk of long-term sequelae. Early prediction of its occurrence is very important to improve the outcomes of the childhood encephalitis. However, the relationship between red blood cell distribution width (RDW) and encephalitis remains unclear. We aimed to explore the association between RDW and encephalitis using a Chinese Pediatric Intensive Care Unit (PICU) database.MethodsIn a cross-sectional study, we analyzed a China-based PIC database spanning from 2010 to 2018. Children admitted to the PIC with encephalitis were included as participants to investigate the correlation between RDW and children encephalitis. Additionally, multifactorial logistic regression, restricted cubic spline analysis models and stratified analyses were utilized to evaluate this relationship.ResultsA total of 10,185 participants were enrolled, among whom the encephalitis prevalence was 1.7% (173/10,185). Multivariate regression models revealed that encephalitis in Chinese children was significantly decreased by 18% with 1% increase in RDW after adjusting for all covariates (Adjusted OR = 0.82, 95% CI: 0.73–0.92). When the RDW was analyzed using quartiles. The adjusted OR (95% CI) of encephalitis for participants in the highest RDW Q4 (≥15.9%) were 0.44 (0.23–0.85), respectively. Compared with individuals with lower RDW Q1 ( ≤ 13%; P for trend = 0.011). The association between RDW and childhood encephalitis was stable in the different subgroups (P for interaction >0.05). Interaction analysis revealed no interactive role in the association between RDW and encephalitis of the childhood.ConclusionsOur study indicated that higher RDW independently associated with reduced encephalitis prevalence in critically ill Chinese children. Validation through multicenter prospective studies is warranted to establish RDW's clinical utility.